2018
DOI: 10.3390/ijms19103184
|View full text |Cite
|
Sign up to set email alerts
|

Novel C15 Triene Triazole, D-A Derivatives Anti-HepG2, and as HDAC2 Inhibitors: A Synergy Study

Abstract: A series of novel C15 urushiol derivatives were designed by introducing a pechmann structure and F-, Cl-, and Br-nitro substituents with different electronic properties into its alkyl side chain, as well as a triazolyl functional group in its aromatic oxide. Their chemical structures were determined based on the analysis of the NMR (nuclear magnetic resonance) spectroscopic and mass spectrometric data. The results showed that compound 4 exhibited a strong inhibition of the HepG2 cell proliferation (half maxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The results suggested a tremendous increase in the number of G2/M phase cells compared to the S phase and G0/G1, clearly indicating that Pimaric acid induced G2/M phase cell cycle arrest. Cell cycle arrest has been reported by levopimaric acid in human hepatoma cells (Qi et al, 2018). Western blotting analysis also showed that the expression of Cyclin-B1 diminished after increasing the molecule concentrations.…”
Section: Discussionmentioning
confidence: 70%
“…The results suggested a tremendous increase in the number of G2/M phase cells compared to the S phase and G0/G1, clearly indicating that Pimaric acid induced G2/M phase cell cycle arrest. Cell cycle arrest has been reported by levopimaric acid in human hepatoma cells (Qi et al, 2018). Western blotting analysis also showed that the expression of Cyclin-B1 diminished after increasing the molecule concentrations.…”
Section: Discussionmentioning
confidence: 70%
“…N-(2-amino-5-substituted phenyl) benzamide significantly induced HCT116 cell death by specifically targeting HDAC2 ( 62 ). In addition, the effects of C15 urushiol and its triazole derivatives on the apoptosis of liver cancer cells have been qualitatively and quantitatively verified ( 132 ). Venturelli et al ( 133 ) reported that 6- and 8-prenylnaringenin enter into the 'foot pocket' of HDAC2 and combine with zinc ion of their catalytic center, subsequently inhibiting excessive proliferation of melanoma cells.…”
Section: Hdac2 In Liver Diseasementioning
confidence: 95%
“…Target compound SF5-SAHA was obtained in high yield (87%) from SF5-SAHEt in aqueous hydroxylamine under basic conditions. Hence, the search for new HDAC inhibitors with improved activities has become a relevant and prospering field of anticancer research and several HDAC inhibitors with promising effects on prostate cancer and liver cancer were recently described [4][5][6][7][8].…”
Section: Chemistrymentioning
confidence: 99%
“…However, severe drawbacks have emerged during the clinical application of single HDAC inhibitors such as intrinsic or acquired drug resistance. Hence, the search for new HDAC inhibitors with improved activities has become a relevant and prospering field of anticancer research and several HDAC inhibitors with promising effects on prostate cancer and liver cancer were recently described [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation